ANALISIS POLA SALURAN DAN MARGIN PEMASARAN GABAH DI KECAMATAN TELUK GELAM KABUPATEN OGAN KOMERING ILIR - Oktriana, Devi; Purba, Yudhi Zuriah Wirya; Saleh, Wardi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
This study aims to analyze the marketing channel patterns and marketing margins of unhusked rice (gabah) in Teluk Gelam District. The research was conducted in three villages: Cinta Marga, Benawa, and Penyandingan, using a quantitative approach through survey methods. A total of 105 rice farmers were selected using simple random sampling, while marketing actors were identified through snowball sampling techniques. Data were analyzed using both qualitative descriptive and quantitative methods to describe marketing channel patterns, calculate marketing margins, and determine the farmer’s share. The results showed two marketing channel patterns: a direct channel from farmers to rice mills, and an indirect channel through collecting traders. The direct channel had a lower marketing margin (IDR 4,500/kg) but offered a higher selling price to farmers compared to the indirect channel (IDR 5,000/kg). Therefore, the direct channel is considered more profitable for farmers. It is recommended to strengthen the direct marketing channel, shorten the distribution chain, and improve farmers’ capacity in market access and price information through training and institutional support. These efforts are crucial to developing a more efficient, equitable, and sustainable rice marketing system.